2020
DOI: 10.1111/ina.12608
|View full text |Cite
|
Sign up to set email alerts
|

Cool but dangerous: How climate change is increasing the risk of airborne infections

Abstract: Cool but dangerous: How climate change is increasing the risk of airborne infectionsLess obvious but more certain and immediate than future droughts and floods, the escalating use of air conditioning (AC) globally is directly resulting in conditions favoring increased person-to-person transmission of airborne infections such as tuberculosis (TB), influenza (flu), and measles. Unlike the gradual environmental effects of increased CO 2 emissions, the impact of AC on airborne infection is nearly instantaneous. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…Incident irradiance (fluence) was measured for each well separately using Ocean Optics USB4000 spectroradiometer with fiber core diameter of 600 μm (QP600-2-VIS-NIR), the small footprint of the fiber optic end allowing accurate measurements. To this end, a printout of the 24-well plate was placed under the UV LED system and the spectroradiometer optic fiber end was placed on the geometric center of the measured well on the printout, perpendicular to the surface and facing the UV LEDs [ 2 ]. Height was adjusted to confirm that the fiber end was in the same distance from the UV LED as was the plate bottom in the irradiation experiments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Incident irradiance (fluence) was measured for each well separately using Ocean Optics USB4000 spectroradiometer with fiber core diameter of 600 μm (QP600-2-VIS-NIR), the small footprint of the fiber optic end allowing accurate measurements. To this end, a printout of the 24-well plate was placed under the UV LED system and the spectroradiometer optic fiber end was placed on the geometric center of the measured well on the printout, perpendicular to the surface and facing the UV LEDs [ 2 ]. Height was adjusted to confirm that the fiber end was in the same distance from the UV LED as was the plate bottom in the irradiation experiments.…”
Section: Methodsmentioning
confidence: 99%
“…SARS-CoV-2, the causal agent of COVID-19, is not only contagious through respiratory droplets, but can also spread through nasal, oral and eye mucus-contaminated surfaces [ 1 ]. Moreover, it has recently been suggested that SARS-CoV-2 could be airborne [ 2 ], although clear evidence for such transmission has not yet been presented. Furthermore, SARS-CoV-2's ability to survive in aerosols for at least 3 h and up to 72 h on plastic surfaces was recently demonstrated [ 3 ], suggesting long-term infection risk from such.…”
Section: Introductionmentioning
confidence: 99%
“…The most common and growing type of air conditioning, ductless or split systems, provide no outside air ventilation. The result of closing windows and turning on ductless air conditioning is a steep rise in rebreathed air fraction (RAF)—that fraction of a breath recently exhaled by others—a good correlate of risk of airborne infection (19). RAF is reasonably well estimated by ambient CO 2 levels (20).…”
Section: Airborne Transmission and The Role For In‐room Air Disinfectionmentioning
confidence: 99%
“…RAF is reasonably well estimated by ambient CO 2 levels (20). A recent demonstration showed a doubling of RAF and risk of infection within an hour of closing a window and turning on the split system AC (19).…”
Section: Airborne Transmission and The Role For In‐room Air Disinfectionmentioning
confidence: 99%
“…The recent pandemic of SARS-CoV-2, the causal agent of COVID-19, is not only contagious through respiratory droplets but can also spread through nasal, oral and eye mucus-contaminated surfaces 1 . Moreover, it has recently been suggested that SARS-CoV-2 could be airborne 2 , although clear evidence for such transmission has not yet been presented. Furthermore, SARS-CoV-2's ability to survive in aerosols for at least 3 h and up to 72 h on plastic surfaces was recently demonstrated 3 , suggesting long-term infection risks.…”
Section: Introductionmentioning
confidence: 99%